THE EFFECT OF BRAND PREFERENCE AND BRAND CONVICTION ON CONSUMER LOYALTY OF EXCELSO CAFE - Indriastuti, Herning Herning (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study intends to analyze and explain the effect of brand preference and brand conviction on consumer loyalty in Excelso Café Samarinda. The samples are consumers of Excelso Cafe. The sampling technique used a probability sampling technique with a simple random sampling method. The numbers of samples are 120 respondents. The analysis was carried out using SPSS. The results of this study indicate that: (1) Brand preference positive and significant effect on consumer loyalty, (2) Brand conviction positive and significant effect on consumer loyalty